Peran Biaya Bahan Baku Dan Biaya Tenaga Kerja Guna Meningkatkan Produksi Tempe - Tukasno Tukasno; Taufiq Taufiq; Heri Apriyanto (Dinar Islamic Review, 2022)
Research to examine the effect of raw material costs and labor costs on tempe production. This research was conducted in small and medium enterprises in Gunung Terang Village, Bumi Agung District, East Lampung. Retrieval of data using interviews and documentation techniques. Data processing using Multiple Linear Regression. The results showed that raw material costs and labor costs affected the production of tempe in Gunung Terang Village, Bumi Agung District, East Lampung. Companies should pay attention to determining the cost of raw materials, and reduce labor costs so that production increases. Future research can retest this research by adding other relevant variables